Pharmacy Education: An Exploration of Global Competency-Based Education and the Development of a Localised Competency Framework in Kenya - McMullen, Jessica (2024)
Modernisation of health professional education is required globally to meet rapidly evolving healthcare demands. This need is further compounded by anticipated health workforce shortages which are particularly pronounced in low- and middle-income countries. Pharmacists play a key role in the health system, thus underpinning the pressing requirement for pharmacy education to keep abreast of contemporary healthcare needs and create highly skilled competent practitioners capable of meeting those needs. Competency-based education (CBE) is a compelling educational model in which to achieve this due to its emphasis on linking theory to practice and aligning learning outcomes with population needs in a learner-centred approach which focuses on acquiring requisite competencies (skills, knowledge and abilities) rather than course hours or credits. CBE in pharmacy demonstrates a complex landscape influenced by diverse interpretations and implementations. Existing literature discusses various aspects of CBE, including assessment methods, the validity of competency frameworks, and barriers and facilitators to implementation. However, global uptake remains inconsistent. Gaps in the literature are evident in low- and middle-income countries despite the potential for CBE to address needs-based educational reform for pharmacy. The African region demonstrates the lowest growth of the pharmacy workforce worldwide exacerbating the urgency for focused inquiry in this area where relevant literature is limited. The aim of this thesis is to provide evidence on the contemporary practices, challenges and opportunities surrounding the use of CBE in pharmacy education. Secondly, this thesis aims to investigate the applicability of the latest Global Competency Framework (GbcFv2) from the International Pharmaceutical Federation (FIP), and adapt this framework to create a locally relevant competency framework for early-career pharmacists in Kenya. The resulting framework provides a tangible resource that can be used as a tool for pharmacy practice development and educational reform. Additionally, this process yields valuable insights on current pharmacy practice in Kenya and highlights potential areas for advancement by shedding light on priority areas for development. To achieve these aims the thesis comprises of four studies in two parts. The first study, Part 1 Stage (i), of the research is a systematic review of the literature from 2010 to 2021 pertaining to all levels of pharmacy education and training to identify the contemporary features of CBE for pharmacy. A total of 1178 studies were retrieved, 103 were screened and 28 studies met the inclusion criteria from across 14 different countries. Features were identified through an inductive narrative synthesis and compared to themes previously identified in the medical literature. Twenty features, and 21 supporting components of CBE for pharmacy were identified and grouped into 6 central themes; design, systems of instruction and learning methods, feedback and assessment, faculty, resources, and internal and external factors. Moreover, an overarching meta-level theme of a holistic and unified vision and approach for CBE emerged as crucial to the successful utilisation of CBE. Furthermore, a lack of studies originating from Africa and South East Asia was discovered highlighting a need for further research in these regions. The second study, Part 1 Stage (ii) of the research employs a global online survey questionnaire distributed to academic institutions delivering pharmacy and pharmaceutical science programmes. A total of 72 responses from 36 different countries underwent descriptive and inferential statistical analyses of the data relating to how CBE is used currently and the challenges experienced in using the CBE approach was conducted. A thematic analysis of the survey data relating to various challenges with using CBE was carried out in a deductive manner on 679 selected multiple choice option responses, using the features of CBE from stage (i) to contextualise the quantitative survey data to the current literature and provide a deeper understanding of the prevalence of challenges reported for each feature for the purpose of guiding future research and development. Challenges relating to the feature of CBE associated with faculty preparedness for the delivery of CBE was found to be the most frequently encountered obstacle to using CBE (n = 141, 20.8%). Additionally, perceived advocacy for CBE by the professional pharmacy and educational regulatory bodies for pharmacy was found to have a statistically significant (p<0.05) effect on the use of CBE when subjecting the data to a 2-sided Fisher’s exact test. Responses were received from all 6 of the World Health Organization global regions, with the majority originating from Europe (45.8%). A limited number of responses from Africa (2.8%) and South East Asia (2.8%) were observed, reflecting the lack of representation form these regions in the first study and reinforcing the need for focused inquiry in these areas in the field of CBE for pharmacy. The third study, Part 2 Stage (i), is a quantitative online survey questionnaire distributed to practicing pharmacists in Kenya. A total of 130 pharmacists, 72 in patient facing and 58 in non-patient facing roles with an average of 12.6 years of practice experience, ranked the relevance of the behavioural statements in the FIP GbCFv2 to their current practice. The results were presented descriptively and inferential statistical analysis was performed to determine any associations between the relevance ratings for pharmacists grouped in to patient facing (PF) and non-patient facing (NPF) core areas of practice. A high degree of relevance for Kenyan pharmacy practice to the FIP GbCFv2 was demonstrated where 56.1% of the 123 statements in this framework demonstrated a 90% or more agreement in relevance. Inferential analysis using 2-sided Fisher’s exact test found that 17 statements demonstrated a statistically significant (P<0.05) difference across the Pharmaceutical Care and Professional/Personal competency domains between the PF and NPF groups. This suggests that consideration of a pharmacist’s practice setting should be taken into account when assessing perception of relevance within a sector-wide framework. In addition, enhanced use of information technology and error reporting were highlighted as potential priorities for the advancement of pharmacy practice in Kenya. The final study utilised a modified Nominal Group Technique (mNGT) consensus development method, consisting of three rounds of voting and two rounds of discussion, with a panel of nine Kenyan pharmacy stakeholders. The panel included representatives from industry, community pharmacy, professional bodies, academia, research, and pharmacy students. Of 31 total amendments, the majority occurred in the largest, Pharmaceutical Care (PC) cluster (51.6%), followed by the Professional/Personal (PP) cluster (25.8%), the Organisation and Management (OM) cluster (12.9%), and finally the smallest, Pharmaceutical Public Health (PPH), cluster (n=9.7%). Major rewording occurred for 7 statements across the PC (n=3), OM (n=2) and PP (n=3) clusters and one competency title in the PC cluster. New statements (n=2) were added in the PPH and the PC clusters and both related to safe and environmentally friendly disposal of medicines. This process led to the adaptation of the FIP GbCFv2 to reflect local pharmacy practice, resulting in the creation of Kenya’s first competency framework for pharmacists, containing 124 behavioural statements. In agreement with the 3rd study, a high degree of relevance (≥90% agreement) for the FIP GbCFv2 was demonstrated overall and the majority of amendments required were minor (re-numbering or grammatical changes, n=16). However, a gap in the FIP GbCFv2 regarding environmentally sustainable pharmacy practices was identified leading to the addition of 2 new statements. These statements focused on promoting green pharmacy practice and reducing pharmaceutical waste, which were considered critical to addressing Kenya’s unique environmental challenges. The research presented in this thesis offers a comprehensive overview of CBE practices worldwide and identifies gaps in the literature for 2 global regions. The focus on competency framework development in Kenya provides a much needed contribution to the literature in Africa. The robust systematic method adopted to create a tool in the form of a nationally relevant competency framework offers a sustainable resource for the further advancement of CBE and pharmacy practice specific to the Kenyan context. Furthermore, this process demonstrates promise for other countries in this region to carry out similar initiatives and represents the first study of its kind using the FIP GbCFv2 in Africa. The findings in this thesis present a comprehensive overview of modern CBE for pharmacy and puts a spotlight on the importance of a system-wide approach to CBE implementation. Particular focus should be paid to a unified and synergistic collaboration between pharmacy practice, regulation and education, echoing previous research in the closely linked medical field, and emphasising the influence of interconnected external factors on the pharmacy education system.